Relationship between Husband's Support, Family Support and Adjustment to the New Role as a Mother with EventsPostpartum Bluesin the Andalas Health Center Working Area - Fitrayeni, Fitrayeni; Tilana, Dilla Dwi; Lisa, Ulfa Farrah (Journal of Midwifery, 2024)
Postpartum bluesor as it is often calledbaby bluesormaternity bluesis a mild psychological disorder that occurs temporarily, namely 2 days to 2 weeks after giving birth, which is characterized by anxiety, panic easily, fatigue, often blaming yourself and feeling unable to take care of the baby. This research aims to determine the relationship between husband's support, family support and adjustment to a new role as a mother with eventspostpartum bluesin the Andalas Health Center working area. Quantitative research by designcross-sectional,carried out in the working area of the Andalas Health Center, Padang City from January to December 2021. The respondents of this study were 58 pregnant women in the third trimester of July. Sampling is carried out using techniques proportional sampling. The research instrument used was a questionnaire. Univariate and bivariate analysis usingchi square (p